Moderasi Beragama dalam Perspektif Keberagaman - Afif Ulin Nuhaa, Muhamad; Putra Satrio, Andhika; Abdul Ro’uuf , Muhammad; Umam, Haeryl; Al Irsyad , M. Hanif; Widya Pratiwi, Tika (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2024)
Religious moderation is a key concept in maintaining harmony amidst religious and cultural diversity. This article aims to explore the role of religious moderation as a strategy to face the challenges of diversity in a pluralistic society. The main issues raised are how attitudes of extremism, exclusivism and intolerance can threaten social cohesion and peace, and to what extent moderate moderation can be an effective solution. This research was carried out through a literature study with a qualitative approach. The results of this research show that religious moderation is able to strengthen social solidarity through an inclusive approach, tolerance and recognition of diversity. In conclusion, diverse moderation is needed as a basis for harmonious living with the support of tolerant education and an active role in society and religious leadership.